New Thermal and Microbial Resistant Metal-Containing Epoxy Polymers - Tansir Ahamad; Saad M. Alshehri (Bioinorganic Chemistry and Applications)
A series of metal-containing epoxy polymers have been synthesized by the condensation of epichlorohydrin (1-chloro-2,3-epoxy propane) with Schiff base metal complexes in alkaline medium. Schiff base was initially prepared by the reaction of 2,6 dihydroxy 1-napthaldehyde and o-phenylenediamine in 1  :  2 molar ratio and then with metal acetate. All the synthesized compounds were characterized by elemental, spectral, and thermal analysis. The physicochemical properties, viz., epoxy value, hydroxyl content, and chlorine content [mol/100 g] were measured by standard procedures. The antimicrobial activities of these metal-containing epoxy polymers were carried out by using minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods against S. aureus, B. subtilis (Gram-positive bacteria), and E. coli, P. aeruginosa (Gram-negative bacteria). It was found that the ECu(II) showed higher antibacterial activity than other metal-chelated epoxy resin while EMn(II) exhibited reduced antibacterial activity against all bacteria.